Augmentorium devices: A sanitation tools for control fruit flies and augmentation parasitoids of fruit flies on chilli plants - Wildan Muhlison; Irwanto Sucipto; Ahmad Tantowi; Muhammad Usman; Ichsan Luqmana Indra Putra (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2026)
Fruit flies, Bactrocera spp. (Diptera: Tephritidae), cause severe yield losses in chili production and conventional insecticide-based control raises environmental and resistance concerns. To our knowledge, this study was the first field evaluation in Indonesia to measure the mesh size threshold for an augmentorium that simultaneously retains newly emerged adult Bactrocera insects and allows for the release of naturally occurring parasitoids. This research aimed to identify fruit fly parasitoid species found in chili (Capsicum frutescens L.) fields and recommend mesh sizes that would enable parasitoids to pass through augmentation devices. This study was conducted in Balung District and the Agrofarmaka Laboratory of Jember University, Jember Regency, East Java, Indonesia. Infested chili fruits were placed in augmentorium devices fitted with four mesh diameters 0.5 mm/32 Mesh; 0.75 mm/24 Mesh; 1 mm/16 Mesh; and.5 mm/12 Mesh. Observations were made by identifying parasitoid species and counting the number of emerging parasitoids. The results showed the presence of two parasitoids, Psyttalia fijiensis and Trichopria sp., which successfully emerged from samples and passed through the meshes. P. fijiensis was able to traverse only the largest mesh (1.5 mm), whereas Trichopria sp. passed even the smallest mesh (0.5 mm). Based on these results, the 1.5 mm (12-mesh) augmentorium optimizes its dual function as a sanitation tool for fruit infested with fruit flies and as a parasitoid augmentation in chili cultivation. This evidence supports the practical application of augmentorium as a landscape-scale celement in integrated pest management for Bactrocera spp. is supported by this evidence.